A Mixed-Method Comparative Analysis of BIM Technology Adoption in China’s and Japan’s Construction Sectors - Sucheng Rui; Koji Makanae; Jun Liu; Jianping Wu; Makoto Fujiu; Yuma Morisaki (Buildings)
In Japan and China, the construction industries make significant contributions to GDP (gross domestic product). Due to different socioeconomic backgrounds, the construction industries in both countries face different challenges. Recently, Japan’s and China’s construction industries have been focusing on the active development of BIM (building information modeling) technology. Recognized for its unique advantages, BIM technology is considered by both countries as an innovative tool that can be used to resolve industry bottlenecks. This paper presents a comparative study on the application of BIM technology in the construction industries of Japan and China, covering five dimensions: development status, policy framework, specific case applications, SWOT analysis, and awareness in higher education. The results indicate that BIM development in both countries is at a broadly similar stage. However, differences in their construction industries have led to distinct strengths and limitations in BIM application. China holds a comparative advantage in policy-driven promotion, while Japan excels in lifecycle management and operational sustainability. Nevertheless, BIM implementation in China tends to be formalistic, whereas Japan needs to enhance its efforts in BIM education. This study discusses improvement measures and complementary strategies based on these differences, aiming to address existing research gaps and underscore their significance in advancing BIM technologies as well as the construction industries of both countries.